Child play and caregiver support to promote convalescence following severe acute malnutrition in Zimbabwe: The Tamba‐SAM pilot study - Jacqueline Kabongo; Louisa Mudawarima; Florence D. Majo; Anesu Dzikiti; Joice Tome; Bernard Chasekwa; Batsirai Mutasa; Lloyd Dzapasi; Epiphania Munetsi; Isabella Cordani; Robert Ntozini; Lisa F. Langhaug; et al. (Maternal and Child Nutrition)
Abstract Children hospitalised for severe acute malnutrition (SAM) have a high risk of mortality, relapse and rehospitalisation following hospital discharge. Current approaches fail to promote convalescence, or to address the underlying social determinants of SAM, meaning that restoration of long‐term health, growth and neurodevelopment is not achieved. Although guidelines recommend play and stimulation to promote recovery, most caregivers are not supported to do this at home. We set out to evaluate the feasibility and acceptability of a codesigned intervention package aimed at providing child stimulation through play, and strengthening caregiver capabilities through problem‐solving skills, peer support and income‐generating activities. We evaluated the intervention in two phases, enroling 30 caregiver–child pairs from paediatric wards in Harare, Zimbabwe, once children who had been hospitalised with SAM were ready for discharge. Children were median 17.8 months old, and 28.6% had human immunodeficiency virus. Trained intervention facilitators (IFs)—lay workers whose own children had previously had SAM—delivered the intervention over 12 weeks with nurse supervision. Qualitative interviews with caregivers and IFs showed that the intervention was feasible and acceptable. Participants reported benefiting from the psychosocial support and counselling, and several started income‐generating projects. Caregivers appreciated the concept of play and caregiver–child interaction, and all reported practising what they had learned. By Week 12, caregiver mental health and caregiver–child interaction improved significantly. Overall, the intervention was feasible, acceptable and showed promise in modifying caregiver knowledge, attitudes and practice. An efficacy trial is now needed to evaluate whether the intervention can improve child convalescence following complicated SAM.